2019
DOI: 10.4103/eus.eus_64_18
|View full text |Cite
|
Sign up to set email alerts
|

Drainage of the right liver under EUS guidance: A bridge technique allowing drainage of the right liver through the left liver into the stomach or jejunum

Abstract: Background and Objective: EUS-guided biliary drainage is now comparable to percutaneous drainage. This technique can be used in cases of complex drainage of the hilum, mainly for salvage therapy to drain the left liver. In cases of inaccessible papilla or altered anatomy, EUS-guided biliary drainage for hilar stenosis of the liver could be used as the first approach. However, this technique has limited applicability for the right liver. In this feasibility study, we reported drainage of the right … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 17 publications
0
14
0
2
Order By: Relevance
“…In this situation, several studies have demonstrated the feasibility of the bridge technique. [ 24 25 ] Another indication for EUS-HGS alone as the initial drainage method is complex hilar strictures associated with significant invasion of the hilum and right liver since this situation is associated with a high risk of ERCP failure. The advantage of EUS-HGS is that this method can be applied as a rescue technique after ERCP failure,[ 8 9 ] early in the case of cholangitis or at a distance when there is disease progression [ Figure 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this situation, several studies have demonstrated the feasibility of the bridge technique. [ 24 25 ] Another indication for EUS-HGS alone as the initial drainage method is complex hilar strictures associated with significant invasion of the hilum and right liver since this situation is associated with a high risk of ERCP failure. The advantage of EUS-HGS is that this method can be applied as a rescue technique after ERCP failure,[ 8 9 ] early in the case of cholangitis or at a distance when there is disease progression [ Figure 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bismuth type II–IV cholangiocarcinoma was a negative predictive factor for endoscopic procedure efficacy and was not related to the lack of adequate drainage in our patients. In all patients whose malignant lesion involved the liver hilum, access to the right intrahepatic duct was gained via the stricture being splinted by a stent introduced into the left intrahepatic duct via the stomach, as previously described [ 29 , 30 ]. The presence of metastatic lesions in the liver and high blood bilirubin levels also had a negative effect on treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In all patients whose malignant lesion involved the liver hilum, access to the right intrahepatic duct was gained via the stricture being splinted by a stent introduced into the left intrahepatic duct via the stomach, as previously described. [29,30] The presence of metastatic lesions in the liver and high blood bilirubin levels also had a negative effect on treatment outcomes. Both ndings might have had a common denominator.…”
Section: Discussionmentioning
confidence: 99%